An examination of the correlation between peat soil characteristics and the growth of sago palm (metroxylon sagu) - Asraff Julaihi, Khan (Universiti Malaysia Sarawak (UNIMAS), 2004)
Sarawak has about 1.6 million hectares ofpeatland and this represents 13% of the state's total land area. Peatlands, in particular the coastal peatlands of Sarawak are very important for agricultural and other land use. Approximately 535,000 ha or about 32% of the total peatland in Sarawak have been converted to oil palm, forest plantation, sago, paddy, pineapple and tapioca plantation. Peat soils are usually waterlogged with very low pH and lack of nutrient contents. Due to these inherent characteristics, they are only suitable for crops with shallow rooting and fibrous root system. Sago palm (Metroxylon sagu) is one of the most intensive agricultural developments on peat. The uniqueness of this plant is its capability to tolerate high acidity and flooding condition in the peat swamps. Because of its natural adaptation, the State government has invested a great deal of money to tap its economic potential on peat. However, the eventual development has brought to light many unanticipated problems, one of which is the trunking ability of the sago palms. In this context, a study was carried out at the Dalat Sago Plantation, in Mukah Division to compare the physical and -chemical properties of peat in relation to the growth pattern of trunking and non-trunking sago palms. The parameters selected for this study were pH, bulk density, degree of humification, soil depth, total ash content, rubbed fibre content, total nitrogen, total potassium, available phosphorus and CEC. The plant growth parameters measured were palm height, dbh, number of suckers and length of the longest frond. The study showed that both the physical and chemical properties differ with peat depth. Better peat properties were found in the trunking plantation plot. For example higher concentration of nutrients (N, P and K) and ash contents were measured in the trunking plot. Further study is nevertheless recommended to determine the relationship between the soil characteristics and the pattern of sago growth and yield.